Control System UV-C Lamp and Room Temperature Based Internet of Things - Rosad, Fitratur Farhan; Mudzakkir Ridwan, Azwar; Faroqi, Adam (CoreID Journal, 2024)
At the beginning of 2020, the world was shocked by the emergence of a new virus, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-nCoV- 2) and the name of the disease is Coronavirus Disease 2019 (COVID-19). Common symptoms of COVID-19 are acute respiratory distress, fever, cough and shortness of breath. One of the efforts to overcome the transmission of COVID-19 is by sterilizing the room. This research designs an automatic room sterilization device using UV-C lamps that can be controlled using the Blynk application. There are 2 working principles of this tool, namely automatic, the lamp will turn on according to a predetermined setpoint and manual, the lamp will turn on manually like a normal lamp. Hardware used to make this tool are NodeMCU ESP8266, DHT11 sensor, PIR sensor, UV-C lamp, and Relay. As for the software used are Arduino IDE and Blynk Application. This research has 3 tests, the first is testing the lamp automation system where the UV-C lamp response is in accordance with the notification in the Blynk application. The second test is a human detection system with a PIR sensor where the sensor can detect with a maximum radius of 5m. The third test of room temperature monitoring system with DHT11 sensor with digital thermometer comparison tool. The average error value is 0.88% with the accuracy of the DHT11 sensor of 99.12%